ECTOPARASITES AND THEIR IMPACT ON CHILDREN'S HEALTH - Fotima Sharipovna Nazarova; Alimova Shohsanam Dilshod qizi (Western European Studies, 2025)
This article provides a comprehensive overview of the main types of ectoparasites commonly found in children, highlighting their morphological and biological characteristics. The impact of parasites on the child’s body, including itching, allergic reactions, skin diseases, and the mechanisms of transmission of dangerous infectious diseases, is analyzed from a scientific perspective. The article also emphasizes the role of hygiene practices in protecting children's health, preventive measures against parasites, and the significance of modern treatment methods in pediatric practice. This study is useful for students specializing in pediatrics, medical professionals, and general readers, as it helps strengthen both theoretical and practical knowledge in the fight against ectoparasites.
Keywords: allergic reaction; dermatitis; endoparasite; Anopheles